2021
DOI: 10.3390/mi12080926
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Microstructured Surface Topologies for the Promotion of Marine Bacteria Biofilm

Abstract: Several marine bacteria of the Roseobacter group can inhibit other microorganisms and are especially antagonistic when growing in biofilms. This aptitude to naturally compete with other bacteria can reduce the need for antibiotics in large-scale aquaculture units, provided that their culture can be promoted and controlled. Micropatterned surfaces may facilitate and promote the biofilm formation of species from the Roseobacter group, due to the increased contact between the cells and the surface material. Our r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 43 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…As mentioned above, the outcome of a preliminary study by the authors 34 showed increased biomass growth on micro-structured Si surfaces over planar reference surfaces in batch reactors with magnetic stirring to emulate shear stress, and with no continuous supply of nutrients, but with rather weak significance levels. To rectify these shortcomings, this study was carried out in microfluidic flow cells, of the type shown in Fig.…”
Section: Methodsmentioning
confidence: 89%
See 2 more Smart Citations
“…As mentioned above, the outcome of a preliminary study by the authors 34 showed increased biomass growth on micro-structured Si surfaces over planar reference surfaces in batch reactors with magnetic stirring to emulate shear stress, and with no continuous supply of nutrients, but with rather weak significance levels. To rectify these shortcomings, this study was carried out in microfluidic flow cells, of the type shown in Fig.…”
Section: Methodsmentioning
confidence: 89%
“…Likewise, in a preliminary study the authors reported on Phaeobacter inhibens biolm formation in batch reactors on micro structured Si surfaces, and found that both honeycomb pillar arrays and honeycomb pit arrays showed increased biomass formation over planar reference surfaces. 34 This study aims to demonstrate TDA biosynthesis on microstructured surfaces and to explore the potential of such biosynthesis in aquaculture disease control.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation